The Impact of Innovation Capability in Increasing Enterprise Performance: Moderated by YouTube Media in Indonesia - Yang, Marvello (Technology, Business and Entrepreneurship, 2023)
This study aim is to investigate how the role of moderation by YouTube affects Innovation capability to Enterprise performance in Indonesia. Dynamic capabilities become a key to be had a sustainable competitive advantage, the author focuses on a moderator of YouTube in revolution 4.0 of high technology. Hypotheses were research data on 244 of YouTubers in Indonesia and the methodology of this analyses by using the regression-based process macro approach method. Bias and endogeneity testing responses were also conducted to confirm the reliability and validity of the findings. This paper provided a further finding the role Moderation of YouTube affected Innovation capability on enterprise performance in Indonesia. This result also confirmed that digitalization helps new start-ups which limited budged and small capital to run their business globally. The dynamic capability runs a role in using high technology and it becomes popular for all knowledge improvement particularly YouTube enables all people around the world at SMEs can communicate, get knowledge sharing, improve idea creativity, and information to their business performance. Therefore, Innovation has a big deal to increase the dynamic capability of SMEs in Indonesia.